Experiments and Simulations of Fully Hydro‐Mechanically Coupled Response of Rough Fractures Exposed to High‐Pressure Fluid Injection. Issue 2 (7th February 2018) - Vogler, D.; Settgast, R. R.; Annavarapu, C.; Madonna, C.; Bayer, P.; Amann, F.
Abstract: In this work, we present the application of a fully coupled hydro‐mechanical method to investigate the effect of fracture heterogeneity on fluid flow through fractures at the laboratory scale. Experimental and numerical studies of fracture closure behavior in the presence of heterogeneous mechanical and hydraulic properties are presented. We compare the results of two sets of laboratory experiments on granodiorite specimens against numerical simulations in order to investigate the mechanical fracture closure and the hydro‐mechanical effects, respectively. The model captures fracture closure behavior and predicts a nonlinear increase in fluid injection pressure with loading. Results from this study indicate that the heterogeneous aperture distributions measured for experiment specimens can be used as model input for a local cubic law model in a heterogeneous fracture to capture fracture closure behavior and corresponding fluid pressure response. Key Points: Experimental measurements of mechanical fracture closure and fluid flow in rough fractures are presented A method to predict fully hydro‐mechanically coupled effects in rough fractures is demonstrated Mechanical fracture closure behavior and corresponding fluid pressure response are captured by numerical simulations